2015
DOI: 10.1111/aor.12471
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factor Analysis for Gastrointestinal Bleeding and Pump Thrombosis in Left Ventricular Assist Device Recipients

Abstract: Left ventricular assist devices (LVADs) are associated with hemostatic complications. We describe the incidence and risk factors for gastrointestinal bleeding (GIB) and pump thrombosis (PT) to optimize patient selection/management. An IRB-approved retrospective review of first LVAD implants between October 1, 2011 and September 30, 2013 at a single center was conducted. Endpoints included epidemiological and risk factor analyses for GIB and PT. Descriptive statistics, chi-squared, and t-tests were used. Sixty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 13 publications
3
16
0
1
Order By: Relevance
“…29 Finally, one of the most disconcerting complications seen in continuous flow LVAD recipients is chronic gastrointestinal bleeding, which often results in withholding anticoagulation. 30 This practice may also have implications for pump thrombosis under circumstances where flow patterns across the pump bearing are not optimized.…”
Section: Discussionmentioning
confidence: 99%
“…29 Finally, one of the most disconcerting complications seen in continuous flow LVAD recipients is chronic gastrointestinal bleeding, which often results in withholding anticoagulation. 30 This practice may also have implications for pump thrombosis under circumstances where flow patterns across the pump bearing are not optimized.…”
Section: Discussionmentioning
confidence: 99%
“…A diversity of information has been published surrounding the association between international normalized ratio (INR) values and CF‐LVAD–related GIB. Researchers found no significant difference in INR values between patients who developed GIB and those who did not (INR 2.21 vs 2.27, respectively; p=0.67) in 64 patients with CF‐LVADs. A multivariate analysis evaluating major bleeding in patients with the Heartmate II (HMII; Thoratec, Pleasanton, CA) device (a CF‐LVAD) demonstrated that INR was not predictive of the development of GIB .…”
Section: Pathophysiologymentioning
confidence: 98%
“…A multivariate regression analysis showed that the odds of GIB were 20.5 times greater in patients aged > 65 years compared to their younger counterparts . In a single‐center evaluation, patients who developed GIB had slightly higher pump speeds, lower creatinine clearance, and increased frequency of infection . One group noted that elevated pulmonary artery pressures and total bilirubin levels were also predictive of developing bleeding events.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…PumpenthrombusAnzeichen einer suboptimalen Antikoagulation und möglichen Bildung eines Pumpenthrombus sind v. a. ein Anstieg der Laktatdehydrogenase (LDH;[16]) als Marker für den Zelluntergang und eine Zunahme des freien Hämoglobins als Zeichen einer Hämolyse. Freies Hämoglo-bin tritt im Plasma auf, wenn die Haptoglobinbindungskapazität erschöpft ist.…”
unclassified